NOTHING IS CERTAIN BUT DEATH – SCENARIOS OF THE MORTALITY IN GERMANY UP TO 2060 - Zimmer, Anna (My University, 2023)
This thesis deals with the developments in mortality in Germany in 2060 and the resulting implications for policymaking. The topic of this thesis is located in the discipline of demography, but the methodological approach of foresight methods is rooted in future studies. This research aims to reduce uncertainty about mortality trends in Germany in the coming decades by providing planning bodies and policymakers with insights into future healthcare needs. The topic is approached through two research questions. 1. How will mortality patterns transform under the influence of climate change and lifestyle change in Germany in 2060? 2. Which measures could be suitable for reacting to the transformations under investigation? The data gathering to answer the research questions was carried out in two iterations of a policy Delphi process. The expert panel on Mortality in Germany in 2060 consisted of a total of 16 researchers with predominantly medical backgrounds and expertise in at least one of the relevant fields to the study, namely public health, environmental health, lifestyle medicine, demography, epidemiology, and healthcare policy. The data from the first round was analyzed using a mixed-methods approach of cluster analysis and conventional qualitative content analysis. Scenarios presented the data results based on the identified clusters through the quantitative data and the storylines drawn from the qualitative data. In total, five scenarios - Mental Health Inferno, Socio-economic Mortality Patterns, Disturbed Human-Environment Relationship, Anticipatory Policy, and Gender-Specific Health – were derived. The scenarios covered causes of death composition from 12 categories clustered according to ICD-10 standards, life expectancy forecasting, as well as risk and life-prolonging factors of lifestyle and climate change. In the second policy Delphi round, the expert panel formulated policy recommendations for each scenario, which were analyzed using conventional qualitative content analysis. The key finding of this study was that life expectancy is projected to rise slower than in all other findings presented in the literature review. Some estimations from the panel even predicted a stagnating or declining trend of life expectancy in Germany in 2060 compared to 2020 under the influence of lifestyle developments and climate change.

Die vorliegende Arbeit beschäftigt sich mit der Entwicklung der Sterblichkeit in Deutschland im Jahr 2060 und den daraus resultierenden Implikationen für die Politik. Das Thema dieser Arbeit ist in der Disziplin der Demografie angesiedelt und ihr methodischer Ansatz in der Zukunftsforschung verwurzelt. Ziel ist es, zur Reduktion der Unsicherheit über die Sterblichkeitsentwicklung in Deutschland in den kommenden Jahrzehnten beizutragen und der öffentlichen Verwaltung sowie den politischen Entscheidungsträgern Erkenntnisse über den möglichen künftigen Bedarf an medizinischer Versorgung bereitzustellen. Zwei Fragestellungen sind maßgeblich: 1. Wie werden sich die Sterblichkeitsmuster unter dem Einfluss des Klimawandels und der Veränderung des Lebensstils in Deutschland im Jahr 2060 verändern? 2. Welche Maßnahmen könnten geeignet sein, auf die untersuchten Veränderungen zu reagieren? Die Datenerhebung wurde in einem zweistufigen policy Delphi-Verfahren durchgeführt. Das hierfür eingesetzte Expertengremium zur Mortalität in Deutschland 2060 bestand aus insgesamt 16 Wissenschaftlern mit überwiegend medizinischem Hintergrund und Fachwissen in mindestens einem der für die Studie relevanten Bereichen. Diese waren Public Health, Umwelt und Gesundheit, Lifestyle-Medizin, Demografie, Epidemiologie und Gesundheitspolitik. Die Daten der ersten Runde wurden mit einem mixed-method Ansatz von Clusteranalyse und herkömmlicher qualitativer Inhaltsanalyse untersucht. Die quantitativ ermittelten Cluster wurden mit Handlungssträngen untermauert, welche sich aus der qualitativen Datenanalyse ermittelt ergaben. Hieraus wurden fünf Szenarien abgeleitet: Mental Health Inferno, Socio-economic Mortality Patterns, Disturbed Human-Environment Relationship, Anticipatory Policy, and Gender-Specific Health. Jedes Szenario beschreibt die Zusammensetzung der Todesursachen auf Grundlage von 12 Kategorien, die nach ICD-10-Standards geclustert wurden, die Vorhersage der Lebenserwartung sowie gesundheitsrelevante Faktoren des Lebensstils und des Klimawandels. In der zweiten policy Delphi-Runde formulierte das Expertengremium für jedes Szenario Politikempfehlungen, die mittels konventioneller qualitativer Inhaltsanalyse ausgewertet wurden. Das wichtigste Ergebnis dieser Studie war, dass die prognostizierte Lebenserwartung langsamer steigen wird als bei allen anderen in der Literaturübersicht vorgestellten Studien. Einige Einschätzungen des Expertengremiums deuten darauf hin, dass die Lebenserwartung in Deutschland bis 2060 möglicherweise nicht nur langsamer steigt, sondern eine stagnierende oder rückläufige Tendenz zeigt, maßgeblich getrieben durch den Wandel im Lebensstil und im Klima. Schlagwörter: Policy Delphi, Szenarien, Mortalität, Deutschland, 2060, Lebensstil, Klimawandel
Keywords: Policy Delphi, Scenarios, Mortality, Germany, 2060, Lifestyle, Climate Change